2010
DOI: 10.1002/mrm.22664
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI‐compatible laparoscopic surgery training simulator

Abstract: During the past few years, laparoscopy has become the gold standard for some surgical procedures and its applications continue to expand. Because of multiple factors such as loss of tactile perception, two-dimensional visualization of the three-dimensional surgical field, and demanding bimanual hand-eye coordination, special training is required to achieve proficiency with laparoscopy. In this study, as the first step toward evidence-based development of strategies to improve the quality of laparoscopy trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Previous research on fNIRS-BCI has focused on modelling patterns of signal amplitude (Coyle et al, 2007;Naito et al, 2007;Power et al, 2012), failing to incorporate functional connectivity data. Here, discriminatory patterns of operator skill level based on functional connectivity have been exposed through the multi-class machine learning approach, and were not revealed with a conventional analytical framework (Bahrami et al, 2011;Leff et al, 2008c;Leff et al, 2008d;Ohuchida et al, 2009). The algorithm for classification of operator skill level states has proven to be accurate, sensitive and specific for detection of operator skill level during LS, regardless of the subtask.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on fNIRS-BCI has focused on modelling patterns of signal amplitude (Coyle et al, 2007;Naito et al, 2007;Power et al, 2012), failing to incorporate functional connectivity data. Here, discriminatory patterns of operator skill level based on functional connectivity have been exposed through the multi-class machine learning approach, and were not revealed with a conventional analytical framework (Bahrami et al, 2011;Leff et al, 2008c;Leff et al, 2008d;Ohuchida et al, 2009). The algorithm for classification of operator skill level states has proven to be accurate, sensitive and specific for detection of operator skill level during LS, regardless of the subtask.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in functional neuroimaging technology have made it possible to monitor operators in more realistic settings and track evolution in brain behaviour that accompanies motor skill levels learning. To this end, there has been an increasing number of research studies focused on studying evoked cortical response to complex motor behaviour in the context of open and minimally invasive surgery (MIS) (Bahrami et al, 2011;Duty et al, 2012;Leff et al, 2007a;Leff et al, 2008a;Leff et al, 2008b;Ohuchida et al, 2009;Zhu et al, 2011). In this study we used functional near-infrared spectroscopy (fNIRS), which has raised increasing interest in recent years for performing less constricted, hence more naturalistic neuroscience experiments (Rodrigo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This FWHM is within the range of values typically used in the fMRI literature and is the starting point for spatial smoothing values adopted in the laboratory, providing an acceptable trade-off between increased sensitivity to detect brain activity, and degradation of spatial resolution. 33 Statistical brain activation maps were calculated using a general linear model (GLM) by convolving a stimulus timing file with a hemodynamic response function (HRF) of arbitrary shape, with the shape determined by the fMRI data. The GLM consisted of 17 regression parameters in total.…”
Section: Iif Image Processingmentioning
confidence: 99%
“…This limitation is affecting research on motor expertise in general ( Mann et al, 2013 ), and different solutions have been suggested and applied for this problem ( Kok and de Bruin, 2017 ). Some studies have investigated surgery with tasks that did require participants to make domain-related movements: For example, Bahrami et al (2011) have built an fMRI-compatible laparoscopic surgery trainer to allow non-expert participants to train surgical movements while being scanned ( Bahrami et al, 2014 ). Morris et al (2015) had participants tie knots on a jig.…”
Section: Discussionmentioning
confidence: 99%